Dispute resolution in the World Trade Organisation - Cameron, James ed. (Cameron May LondonGB, 1998)
Provides an overview of the Dispute Settlement Understanding in a broad legal and economic context. Focuses on the function and some of the specific attributes of the Appellate Body. Examines specific sectors and cases which have become the subject of WTO disputes. Considers other issues and perspectives on WTO dispute settlement, including a developing country perspective, experience with regional trade agreements, and the environmental side agreement to the North American Free Trade Agreement (NAFTA).